Case report: The application of neoadjuvant chemoradiotherapy in anal adenocarcinoma combined with perianal Paget disease involving vulvar skin - Gan-bin Li; Xiao-yuan Qiu; Xiao Zhang; Ning Zhang; Guo-le Lin (Frontiers in Oncology, 2023)
Anal adenocarcinoma combined with perianal Paget’s disease (PPD) involving the vulva is rare, and there is no established standard treatment. We present the case of a 69-year-old woman with symptoms of intermittent hematochezia and perianal discomfort for 7 months. Upon examination, we discovered a plaque-like hard mass on the right posterior wall of the anal canal, which extended to encompass the anus and dentate line. The lesion skin also extended forward from the gluteal groove, involving the bilateral labial area. Colonoscopy revealed an extensive protruding lesion on the dentate line, which was confirmed as anal adenocarcinoma (mrT4N0M0). The presence of Paget’s cells in perianal and vulvar skins led to the diagnosis of PPD. The strategy of neoadjuvant chemoradiotherapy (nCRT) followed by radical surgery was then made after multi-disciplinary discuss. The scope and extent of perianal and vulvar disease were significantly diminished after nCRT. The patient underwent laparoscopic abdominoperineal resection and vulvar lesion resection, confirming the diagnosis of anal adenocarcinoma (ypT2N0). No evidence of tumor cells was found in perianal and vulvar skin, indicating a complete response. The patient is regularly monitored without recurrence or metastasis.